Spx, the central regulator of the heat and oxidative stress response in B. subtilis, can repress transcription of translation-related genes - Schäfer, Heinrich; Heinz, Anja; Sudzinová, Petra; Voß, Michelle; Hantke, Ingo; Krásný, Libor; Turgay, Kürşad (Molecular microbiology, 2019)
Spx is a Bacillus subtilis transcription factor that interacts with the alpha subunits of RNA polymerase. It can activate the thiol stress response regulon and interfere with the activation of many developmental processes. Here, we show that Spx is a central player orchestrating the heat shock response by up-regulating relevant stress response genes as revealed by comparative transcriptomic experiments. Moreover, these experiments revealed the potential of Spx to inhibit transcription of translation-related genes. By in vivo and in vitro experiments, we confirmed that Spx can inhibit transcription from rRNA. This inhibition depended mostly on UP elements and the alpha subunits of RNA polymerase. However, the concurrent up-regulation activity of stress genes by Spx, but not the inhibition of translation related genes, was essential for mediating stress response and antibiotic tolerance under the applied stress conditions. The observed inhibitory activity might be compensated in vivo by additional stress response processes interfering with translation. Nevertheless, the impact of Spx on limiting translation becomes apparent under conditions with high cellular Spx levels. Interestingly, we observed a subpopulation of stationary phase cells that contains raised Spx levels, which may contribute to growth inhibition and a persister-like behaviour of this subpopulation during outgrowth.
Keywords: regulace genové exprese u bakterií; fyziologický stres; reakce na tepelný šok; Oxidative Stress; Gene Expression Regulation, Bacterial; Bacillus subtilis; Stress, Physiological; Transcription, Genetic; Heat-Shock Response; genetická transkripce; proteosyntéza; oxidační stres; Transcription Factors; transkripční faktory; Gene Expression Profiling; stanovení celkové genové exprese; Protein Biosynthesis